2015
DOI: 10.1007/s10815-015-0574-3
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell assay for telomere DNA content shows increasing telomere length heterogeneity, as well as increasing mean telomere length in human spermatozoa with advancing age

Abstract: The marked increase in STL heterogeneity as men age is consistent with a role for ALT during spermatogenesis. No data have yet reported the effect of age on STL heterogeneity. Based on these results, future studies should expand this modest sample size to search for molecular evidence of ALT in human testes during spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 32 publications
1
33
1
Order By: Relevance
“…In adult somatic cells, telomeres are composed of large noncoding sequences of approximately 1000–2000 TTAGGG tandem base pair repeats that end in a 3′ extension past the 5′ terminus [2]. In other select cells, the telomeres are maintained and can be considerably longer, such as adult human germ cells which can contain anywhere from 500–5000 repeats [3,4,5]. During each cycle of cell division telomeres are incompletely replicated, and consequently, their ends are progressively shortened [6].…”
Section: Introductionmentioning
confidence: 99%
“…In adult somatic cells, telomeres are composed of large noncoding sequences of approximately 1000–2000 TTAGGG tandem base pair repeats that end in a 3′ extension past the 5′ terminus [2]. In other select cells, the telomeres are maintained and can be considerably longer, such as adult human germ cells which can contain anywhere from 500–5000 repeats [3,4,5]. During each cycle of cell division telomeres are incompletely replicated, and consequently, their ends are progressively shortened [6].…”
Section: Introductionmentioning
confidence: 99%
“…In mice, Zscan4 expression is characteristic of two‐cell embryos and “2C‐like” embryonic stem cells, featuring rapid telomerase‐independent telomere lengthening (Zalzman et al, ). A previous study suggested that the ALT mechanism could be active during spermatogenesis in humans, based on an unexpected age‐related increase in sperm TL in the absence of telomerase (Antunes et al, ). This mechanism has been described also in the absence of telomerase activity after oocyte fertilization and activation (de Frutos et al, ; Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study published in 2015 [75] reported a marked increase in sperm telomere length heterogeneity as men age and a longer length in samples with normal parameters in comparison with samples with abnormal parameters. These findings could have implications for infertile couples treated with assisted reproduction techniques due to a high probability of shorter telomere length in the offspring, taking into account the reported association between shorter telomere and depression, autism, neoplasia, and general poor health.…”
Section: Telomere Lengthmentioning
confidence: 99%